Novel Triple Diode Solar Cells Equivalent Circuit Models With Lambert W Function Expressions - Martin Calasan; Snezana Vujosevic (IEEE Journal of the Electron Devices Society)
This brief presents two new equivalent circuit schemes for triple-diode solar cell models (TDM). These schemes enable the formulation of an analytical relationship between current and voltage using the Lambert W function. A new Root Mean Square Error (RMSE) formula is also introduced. The models are validated on two solar cells and two panels under different conditions. Results show high accuracy and efficiency.